2010
DOI: 10.3325/cmj.2010.51.74
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Interventions to Prevent Spread of Sexually Transmitted Infections, Including HIV, Among Young People in Europe

Abstract: The young people studied were more accepting of peer-led than teacher-led interventions. Peer-led interventions were also more successful in improving sexual knowledge, though there was no clear difference in their effectiveness in changing behavior. The improvement in sexual health knowledge does not necessarily lead to behavioral change. While knowledge may help improve health-seeking behavior, additional interventions are needed to reduce STIs among young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
(81 reference statements)
1
33
2
Order By: Relevance
“…There have been a large number of systematic reviews that evaluated the effectiveness of these programmes (Chin 2012; Dick 2006; DiClemente 2008; Flisher 2008; Gallant 2004; Harrison 2010; Johnson 2003; Johnson, 2011; Kim 2008; Kirby 2007; Lazarus 2010; Magnussen 2004; Medley 2009; Michielsen 2010; Paul 2008; Shepherd 2010; Yankah 2008), including reviews that have focused solely on school-based interventions (Bennet 2005; Fonner 2014; Kirby 2006; Lopez 2016; Paul 2008), and a review of reviews (Mavedzenge 2013). Many of these reviews have suggested that school- and community-based prevention programmes for adolescents have been effective in delaying self-reported sexual activity, HIV-related preventative behaviours, adolescent pregnancy, and STIs (Chin 2012; Fonner 2014; Johnson 2003; Johnson, 2011; Kirby 2009; Laud 2016), although others have reported less, or mixed, success (Bennet 2005; DiCenso 2002; Lopez 2016 Oringanje 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a large number of systematic reviews that evaluated the effectiveness of these programmes (Chin 2012; Dick 2006; DiClemente 2008; Flisher 2008; Gallant 2004; Harrison 2010; Johnson 2003; Johnson, 2011; Kim 2008; Kirby 2007; Lazarus 2010; Magnussen 2004; Medley 2009; Michielsen 2010; Paul 2008; Shepherd 2010; Yankah 2008), including reviews that have focused solely on school-based interventions (Bennet 2005; Fonner 2014; Kirby 2006; Lopez 2016; Paul 2008), and a review of reviews (Mavedzenge 2013). Many of these reviews have suggested that school- and community-based prevention programmes for adolescents have been effective in delaying self-reported sexual activity, HIV-related preventative behaviours, adolescent pregnancy, and STIs (Chin 2012; Fonner 2014; Johnson 2003; Johnson, 2011; Kirby 2009; Laud 2016), although others have reported less, or mixed, success (Bennet 2005; DiCenso 2002; Lopez 2016 Oringanje 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While these factors are difficult or impossible to modify, knowing them allows nurses to adapt their care to this group's specific risk level. The cognitive and psychosocial factors are important because they are modifiable; these factors include knowledge, attitudes, self-efficacy, subjective norms and sensations seeking (Kirby et al 2011;Lazarus et al 2010;Sales et al 2013). Knowledge provides the foundation for an individual's attitude and is essential to reducing sexual risk-taking behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Background every day about one million patients with curable sexually transmitted diseases (STDs) infected globally, of which 50% affect people under 25 years of age [1]. according to the Joint United Nations Programme on HIV/AIDS (UNaIDS), about 8,900 people are living with HIV/aIDS, and about 1,000 aIDS-related deaths had been reported in Bangladesh by the end of 2014.…”
mentioning
confidence: 99%